Review on UV-LEDs: State of the Art and Challenges Ahead - Samsudin, F. M. E. A.; Zainal, N.; Hassan', Z. (2016)
The latest challenge of LEOs is to residing themselves in advanced ultra-violet (UV) lighting, which involves industrial UV curing (e. coatings , resins. adhesives). medical and scientific (e.g. pl1ototherapy, DNA sensing). sterilization (bacterial disinfection , water purification, skin therapy), security (counterfeit detection and forensics) and horticulture lighting New market research by Markets and Markets reports that the UV LED market is expected to reach USD 369.58 million by 2020. So far , high energy AI,Ga1.xN materials are the best solution to product UV emission LEOs in the wavelength range below 390 nm. Progress on AIXGa1-XN based UV LEOs is on-going with external quantum efficiency (EQE) above than 10% at present. However, the EQE of most of th e UV-B (320-280 nm) and UV-C (280-210 nm) LEOs are still in single-digit percentage range and unable to cope witt1 th e current deep UV lighting market demand. The output power of such LEOs is few mWs while limited lifetime is tess than a thousand hours. From fundamental point of view, producing UV-LEDs below 360 nm requires more AI composition in the AIXGa1-XN based active region and high growth temperature above 11 00°C . Unfortunately, incorporation of AI atoms into the AIXGa1-XN lattice structure is not an easy process as the atoms readily react with oxygen, while parasitic reaction beco mes much more serious at high temperature. These effects significantly kill the overall efficiency of LEDs. In this talk, novel published techniques to solve the above problems will be rev iewed and near-future work in developing UV-LEDs at INOR. USM will be presented.